Persepsi Masyarakat Terhadap Jemaah Salafi (Studi Tentang Tipologi dan Relasi Sosial Jemaah Salafi) - Abdurrohman Abdurrohman; Moh. Syarif Hidayatullah; Nurun Sholeh; Huldiya Syamsiar (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
The emergence of the Salafi movement in Indonesia, carrying the mission of purifying Islamic teachings, is always an interesting subject to study due to its teachings often conflicting with those of mainstream Islamic groups adhering to Ahlussunnah Wal Jama’ah. The aim of this research is to identify the typology and social relations of the Salafi group in Aikmel District. To achieve this objective, the researcher employs a qualitative method with a descriptive approach. This method was chosen to provide an in-depth description of the typology and social relations of the Salafi group in Aikmel District. Data analysis utilizes the qualitative model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The research findings indicate that the community's perception of the Salafi congregation in Aikmel District can be categorized into two typologies. First, there are Salafi congregations that exhibit an exclusive attitude and remain steadfast in their teachings. Sociologically, these Salafi groups avoid building social relations and communication with non-Salafi Islamic groups. Second, there are Salafi congregations that are tolerant and inclusive. This type of Salafi group sociologically demonstrates social sensitivity by showing inclusive, tolerant attitudes, respect, and upholding brotherhood. They participate in religious rituals or practices commonly conducted by non-Salafi Islamic groups, such as the nine-day death tahlilan, the commemoration of the Prophet Muhammad's birthday, and others. This study aims to challenge the stereotype that all Salafi congregations are exclusively rigid in their teachings. It demonstrates that, in Aikmel District, there are also Salafi congregations that are inclusive and tolerant.